Effects of integrated nutrient management on performance of t. aus rice (BRRI dhan48) in old brahmaputra floodplain soil - Kaisar, Nahid; Zofar Md. Moslehuddin, Abu; Mahbubul Alam Tarafder, Md.; Sohanur Rahman, Md. (International Journal of Advanced Geosciences, 2020)
A field experiment was conducted at Sutiakhali, Mymensingh to see the effect of integrated nutrient management on performance of T. Aus rice (BRRI dhan48) during March to July 2015 following Randomized Complete Block Design with five treatments and four replications. The treatments were T1: RD (N75 P12 K45 S9), T2: STB (N74 P11 K36 S7), T3: INM (N54 P5 K27 S5+ CD @ 5.0 t ha−1), T4: Farmer’s practice (N69 P30 K37), and T5: Control (no fertilizer). The highest values for plant height (97.35 cm), effective tillers hill-1(19.45) panicle length (23.49 cm), filled grains panicle-1 (123.7), 1000-grain weight (25.39 g), grain yield (4.823t ha-1), straw yield (8.462 t ha-1) and biological yield (13.29 t ha-1) were obtained from T3: INM. Lowest values found in T5: Control. The maximum N, P, K and S uptake by grain (35.55, 6.99, 15.20 and 3.38 kg/ha respectively) were obtained from the application of INM. The minimum N, P, K and S uptake by grain (20.08, 3.64, 8.35 and 1.74 kg/ha respectively) were found from T5: Control. Similarly, the maximum N, P, K and S uptake by straw (3.38, 5.43, 99.25 and 7.37 kg/ha respectively) were found from T3: INM. The minimum N, P, K and S uptake by straw (1.74, 2.67, 49.70 and 3.87 kg/ha respectively) were obtained from T5 (Control). Among treatments, T3 produced highest grain and straw of BRRI dhan48. Chemical fertilizers in combination with manure based on INM could be recommended for BRRI dhan48 production in aus season.